2018
DOI: 10.3390/metabo8010021
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Assisted Metabolomics

Abstract: Understanding and harnessing the interactions between nanoparticles and biological molecules is at the forefront of applications of nanotechnology to modern biology. Metabolomics has emerged as a prominent player in systems biology as a complement to genomics, transcriptomics and proteomics. Its focus is the systematic study of metabolite identities and concentration changes in living systems. Despite significant progress over the recent past, important challenges in metabolomics remain, such as the deconvolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A glucose-free spectrum is created by subtracting the two spectra, which reveals the hidden metabolites lost behind the glucose signal [28]. Another approach of removing metabolites from an NMR spectrum has been accomplished by using nanoparticles to bind specific metabolites [29] or with NMR shift reagents (e.g., gadolinium, Gd 3+ ) [30,31] that broaden NMR signals due to T 2 relaxation. Enzymatic activity has also been utilized to remove signal interference (e.g., removal of urea from urine with urease) [32,33].…”
Section: Metabolite Quantification In 1d Nmr Metabolomicsmentioning
confidence: 99%
“…A glucose-free spectrum is created by subtracting the two spectra, which reveals the hidden metabolites lost behind the glucose signal [28]. Another approach of removing metabolites from an NMR spectrum has been accomplished by using nanoparticles to bind specific metabolites [29] or with NMR shift reagents (e.g., gadolinium, Gd 3+ ) [30,31] that broaden NMR signals due to T 2 relaxation. Enzymatic activity has also been utilized to remove signal interference (e.g., removal of urea from urine with urease) [32,33].…”
Section: Metabolite Quantification In 1d Nmr Metabolomicsmentioning
confidence: 99%
“…NMs have already started to find a niche in assisting in various metabolomics experiments in which they selectively bind to metabolites and thus concentrate them facilitating identification, as has been extensively reviewed by Zhang Environmental Science: Nano Critical review et al 8 Here, the use of NMs to carry out SERS, solid phase extraction (SPE) metabolite enrichment and for enhancing MALDI-MS ionization of metabolites are discussed in detail. An overview of all the untargeted studies using NMs for selective enrichment, including methods used and metabolites identified can be found in Table 3. 4.4.1 Lipid corona.…”
Section: Untargeted Analysis Of the Metabolite Coronamentioning
confidence: 99%
“…Metabolites are orders of magnitude smaller than proteins, typically below 1000 Da whereas proteins are measured on the kDa scale, and metabolites are typically reactants, intermediaries and products of enzymatic activity. While the idea of interactions between metabolites and NMs is not a new one, as this is one of the applications of surface enhanced Raman spectroscopy (SERS) 7,8 and several approaches to "clean" samples prior to analyses, 8,9 the potential significance of metabolite constituents of the NM biomolecule corona in terms of NMs impacts on molecular signaling pathways and eventual adverse outcome pathways (AOPs) or targeting ability for nanomedicines has yet to be systematically explored.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-assisted diffusometry, for example, relies on nonspecific interactions between the analytes and the surface exposed by chromatographic supports, surfactants, or polymers . On a similar principle, large (20 nm) silica nanoparticles are used as line-broadening agents, with the advantage that they can be converted from anionic to cationic receptors by doping with alumina . In contrast with the aforementioned methods, though, the Au–S chemistry in gold nanoparticles provides a unique route for turning virtually any supramolecular receptor into a nanoreceptor.…”
Section: Introductionmentioning
confidence: 99%